2019
DOI: 10.3390/rs11222705
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Optimal Wavelength for Oceanographic Lidar at the Global Scale Based on the Inherent Optical Properties of Water

Abstract: Understanding the optimal wavelength for detecting the water column profile from a light detection and ranging (lidar) system is important in the design of oceanographic lidar systems. In this research, the optimal wavelength for detecting the water column profile using a lidar system at the global scale was analyzed based on the inherent optical properties of water. In addition, assuming that the lidar system had a premium detection characteristic in its hardware design, the maximum detectable depth using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…LiDAR instruments are among the airborne/spaceborne active RS systems that can obtain depth-resolved information of ocean layers [255]. Satellite LiDAR systems can operate under thin clouds, between holes in broken clouds, and in polar regions to provide global ocean coverage [252].…”
Section: Lidarmentioning
confidence: 99%
See 2 more Smart Citations
“…LiDAR instruments are among the airborne/spaceborne active RS systems that can obtain depth-resolved information of ocean layers [255]. Satellite LiDAR systems can operate under thin clouds, between holes in broken clouds, and in polar regions to provide global ocean coverage [252].…”
Section: Lidarmentioning
confidence: 99%
“…Subsurface ocean measurements have been traditionally conducted using shipborne or airborne instruments [258], [262]- [264]. A specifically designed satellite for oceanographic missions and water column profile data detection has not been launched into space yet, and currently, shipborne and airborne LiDAR systems are employed for ocean studies [255]. Table E summarizes the specifications of spaceborne LiDAR missions.…”
Section: A Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is just a compromise because 532 nm is suitable for coastal water, while it does not work so well in clear open ocean waters that constitute most of the global oceans. It has been shown that a shorter wavelength will be better for open-ocean applications [5,22,26]. However, the estimate of the detection potential capability of spaceborne lidar demands a spaceborne lidar simulator.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several researchers have discussed the laser optimal wavelength, but the impact of background light [26], which may overestimate the penetration depths in open ocean water, has been neglected. Other researchers did not take into account the responsivity of the detector and detector noise [27].…”
Section: Introductionmentioning
confidence: 99%